Embodiment and enculturation: the future of architectural design - Mallgrave, Harry F. (Frontiers in Psychology, 2015)
A half-century ago the Dutch architect Aldo van Eyck encouraged designers to think about “space and time” not as abstractions in themselves but rather as cultural events better approached through the medium of “place and occasion.” Van Eyck made this point on the basis of his own travels and through his extensive readings in cultural anthropology, and his prescience is only now acquiring the credibility that it deserves through the work of a multitude of interdisciplinary researchers. Phenomenologists argue that we are embodied organisms-acting-within-environments, and these inhabiting abodes are constructed of both material and cultural dimensions. We are thus preeminently social in our range of self-consciousness, and intensely ceremonial in every facet of our being. Evolutionary psychologists and anthropologists are currently locating the origin and development of our most basic social behaviors far in our pre-human past; neuroscientists are today modeling our social circuits in the deepest reaches of our brains. Architecture would gain much from an updated cultural theory grounded in these new models of human existence.